Scurvy: Forgotten diagnosis, but still exist. (2020) - Miraj, Faisal; Abdullah, Ali
Highlights: Scurvy is a rare condition in pediatric patients. The rarity and the polymorphisms of the clinical signs and symptoms make scurvy an often unknown or forgotten diagnosis. Extremely rare occurrence of scurvy in modern society at present time, it is difficult to differentiate it from other diseases such as infection. Abstract: Introduction: Scurvy is a rare condition in pediatric patients, resulted from a vitamin C deficiency. Musculoskeletal symptoms occur in 80% of patient. The rarity and the polymorphisms of the clinical signs and symptoms often make scurvy an unknown or forgotten diagnosis. Methods: A 3-years-old boy with limping gait, progressive pain and swelling on his left lower limb since 3 months prior was diagnosed as osteomyelitis based on MRI. When there was no improvement after 2 weeks of IV antibiotic administration, we did surgical debridement procedure. Intraoperative, we found extensive blood clot inside and in the entire periosteum instead of infection. One week after surgery, there was still no improvement clinically and radiographically. Histopathology result suggested a fibro-osseous tumor. After reviewing clinical sign including skin presentation and plain radiology, we suspected scurvy disease in this patient and started a vitamin C therapy course immediately. Results: Two weeks after we started vitamin C treatment, the patient's condition was significantly improved clinically and radiographically. Serial radiograph was taken after 2 and 12 months of surgery, and it showed significant improvement on the site where the previous pathological process appeared. Discussions: Because of the extremely rare occurrence of scurvy in modern society at present, it is difficult to differentiate it from other diseases such as infection. The diagnosis of scurvy is made by careful studies from history taking, physical examination, laboratory and especially radiological finding that show pathognomonic appearance. Examination of vitamin C level serum is a gold standard, but unfortunately not available in our country. Improvement after vitamin C administration also established that condition. Conclusion: Scurvy should have established by clinical and radiological findings that show pathognomonic signs around joint, even without supported by vitamin C serum.